Costruzione e validazione di uno strumento per misurare le pratiche educative Montessori nella scuola primaria italiana - Stefano Scippo (LED Edizioni Universitarie, 2023)
CONSTRUCTION AND VALIDATION OF A TOOL TO MEASURE MONTESSORI EDUCATIONAL PRACTICES IN THE ITALIAN PRIMARY SCHOOL Abstract Maria Montessori began to define her pedagogical proposal in Italy at the beginning of the 20th century. Currently, there are no studies evaluating the effectiveness of Montessori education in her home country (Demangeon et al., 2023). To accomplish this, it is necessary to have a suitable instrument within the Italian context to measure the educational practices of Montessori teachers. In Italy, there is only one checklist developed to observe teachers' actions (Caprara, 2018). This article presents the construction and psychometric validation of a self-reported questionnaire to measure Montessori teachers' practices. The instrument consists of 63 items and was administered to 329 Montessori primary school teachers. The Cronbach's alpha coefficient is 0.927, and an exploratory factor analysis extracted 8 factors that account for 44.8% of the variance. The resulting scale can be used to (a) explore what Montessori teachers do in their classrooms, assessing the gap between ideal and actual Montessori practices, and (b) in a study aiming to evaluate the effectiveness of Montessori education in Italy.